Social commerce website design, perceived value and loyalty behavior intentions: the moderating roles of gender, age and frequency of use. - Molinillo-Jiménez, Sebastián; Aguilar-Illescas, Rocío; Anaya-Sánchez, Rafael; Liébana Cabanillas, Francisco (My University, 2021)
Drawing on the stimulus-organism-response (SOR) framework, a model is tested that improves the understanding of customer loyalty toward social commerce websites. The results showed that: information and service quality are key antecedents of perceived value, whereas rewards and recognition, and customization are non-significant. Perceived value is an important driver of customer loyalty toward these websites. The model’s relationships are affected by gender and frequency of use. Overall, the findings of this study extend the understanding in the social commerce context of: (i) the antecedents of customer perceived value and behavioral intentions; and (ii) the moderating effects of age, gender and frequency of social commerce use on the model relationships.
Keywords: Comercio electrónico; Comunidad; Consumidores - Preferencias; Social commerce; Perceived value; Loyalty